Polymer, prepolymer of polymer, preparation method and application of prepolymer

By forming a complex of natural polysaccharides and dopamine, and forming a protective coating at the bladder wall injury site, the problem of difficulty in relieving and curing interstitial cystitis treatment is solved, and effective repair of the bladder wall and symptom relief is achieved.

CN119569908APending Publication Date: 2025-03-07ARMY MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411623096.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The treatment of interstitial cystitis/bladder pain syndrome is difficult to achieve relief and radical cure. The existing drugs are limited in efficacy and expensive, and have low bioavailability.

Method used

By forming a complex of natural polysaccharides with dopamine, using the inflammatory environment to polymerize in situ, forming a protective coating at the bladder wall injury site, repairing the bladder mucosal barrier.

Benefits of technology

The formed polymer film coating has anti-inflammatory and antioxidant effects, effectively repairing bladder wall damage, alleviating symptoms, and delaying or reversing the disease progression.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569908A_ABST
    Figure CN119569908A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biology, in particular to a polymer, a prepolymer of the polymer, a preparation method and application of the polymer. The invention relates to a polymer. The polymer has a chemical structure as shown in a formula I: # imgabs0 #, wherein x is equal to 1-10; y is equal to 10 to 200; an application of the polymer in preparation of a bladder mucosal lesion repair material; the prepolymer solution of the polymer contains a prepolymer of sodium alginate oligosaccharide and dopamine; the preparation method of the prepolymer of the polymer comprises the following steps: providing sodium alginate oligosaccharide AOS; and adding an activating agent 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDAC), adding a catalyst N-hydroxysulfosuccinimide (NHS), and then adding dopamine hydrochloride (DA) to obtain the prepolymer solution. The polymer disclosed by the invention has good biocompatibility and an in-situ polymerized protective coating with excellent anti-inflammatory and anti-oxidative stress effects, and can effectively recover and improve inflammation, bleeding, edema, fibrosis and hypertrophy of bladder tissues.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biotechnology, and in particular to a polymer, a prepolymer of the polymer, a preparation method and use thereof. Background Art

[0002] Interstitial cystitis / bladder pain syndrome (IC / BPS) is a chronic inflammatory disease with bladder dysfunction. It is a chronic disease with frequent urination, urgency, dysuria, increased nocturia, and chronic pelvic pain as the main clinical manifestations, and urothelial barrier damage and ulcers as pathological characteristics. There is currently no specific diagnostic method, nor is there a treatment method that works well for the majority of patients. How to repair the damaged bladder mucosal barrier, alleviate symptoms, and delay or reverse the course of the disease is the focus of current attention. Intravesical instillation therapy has become an ideal means of administration due to its high local drug concentration and low systemic side effects, which directly affects the lesions. Currently, the drugs used for instillation include lidocaine, heparin, hyaluronic acid, etc. However, the efficacy of intravesical instillation of lidocaine is limited, and it only has an analgesic effect but cannot accelerate the recovery of the disease. Intravesical instillation of cystitis treatment drugs is also affected by urination, resulting in a short drug action time, high price, and low bioavailability.

[0003] The complexity of the etiology and mechanism of IC makes it difficult to achieve complete remission and cure. Various treatment methods, including oral medications, intravesical drug instillations, and surgery, are not very satisfactory and are prone to recurrence. Therefore, a new bladder protective coating is urgently needed as a treatment method. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a polymer, a polymer prepolymer, a preparation method and uses thereof, which solve the technical problem that the complexity of the causes and mechanisms of interstitial cystitis / bladder pain syndrome makes it difficult to achieve relief and cure in its treatment.

[0006] (II) Technical solution

[0007] In a first aspect, an embodiment of the present invention provides a polymer having a chemical structure as shown in Formula I:

[0008]

[0009] Wherein x=1-10; y=10-200.

[0010] Optionally, x=1-10, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10.

[0011] In one embodiment of the present invention, x=2-8.

[0012] In a second aspect, an embodiment of the present invention provides use of the polymer in preparing a bladder mucosal injury repair material.

[0013] In a third aspect, an embodiment of the present invention provides a polymer prepolymer, which contains a prepolymer of sodium alginate oligosaccharide and dopamine.

[0014] Optionally, the polymer prepolymer further contains 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride EDAC as an activator and N-hydroxysulfosuccinimide NHS as a catalyst.

[0015] In a fourth aspect, an embodiment of the present invention provides a method for preparing a prepolymer of a polymer, the preparation method comprising the steps of:

[0016] S1, providing sodium alginate oligosaccharide AOS aqueous solution;

[0017] S2, deoxygenating the alginate oligosaccharide AOS aqueous solution; adding an activator 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride EDAC, stirring; adding a catalyst N-hydroxysulfosuccinimide NHS, stirring; then adding dopamine hydrochloride DA, stirring, dialyzing and purifying after the reaction is complete, and then freeze-drying for 2 days to 6 days to obtain the prepolymer solution.

[0018] Sodium alginate Alg has been widely used in the fields of food, textile, feed processing, and medical treatment. Due to its good biocompatibility, it is mostly used for sustained-release drugs. Due to its high viscosity, it can prolong the release time of drugs, slow down absorption, prolong efficacy, and reduce side effects. Sodium alginate is a natural polysaccharide that is mostly found on the surface of cells. Dopamine containing amino groups has been developed as a small molecule precursor to achieve similar adhesion properties through polymerization. Since the Messersmith team pioneered the adhesion properties of polydopamine to a variety of materials in Science magazine in 2007, polydopamine coatings have been widely used as a bionic method for surface functionalization modification of inorganic and organic materials. The inventors of this application creatively modified dopamine with natural polysaccharides, that is, the complex formed by natural polysaccharides and dopamine was used to treat bladder wall damage caused by interstitial cystitis. The in situ polymerized compound was precisely polymerized at the site of injury using the inflammatory environment to form a protective coating.

[0019] Optionally, the deoxygenation method includes nitrogen bubbling, argon bubbling, excess hydrogen peroxide decomposition period and stirring under vacuum negative pressure.

[0020] Optionally, in step S1, the preparation method of sodium alginate oligosaccharide AOS is: dispersing sodium alginate Alg in distilled water, stirring at 25°C-60°C, adding hydrogen peroxide after complete dissolution, and after complete reaction, dialyzing and purifying the product solution, and then filtering through a cell sieve with a particle size of 0.2-0.44 μm to obtain the product sodium alginate oligosaccharide AOS.

[0021] It should be noted that, in the polymer structure shown in Formula I, x = 1-10, preferably, x = 2-8. The value of x is related to the hydrolysis degree of oligoalginate sodium AOS in step S1.

[0022] Optionally, in step S1, the mass fraction of sodium alginate Alg dissolved in distilled water is 0.5%-2.5%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%.

[0023] In one example of the present invention, the mass fraction of sodium alginate Alg dissolved in distilled water is 1.5%.

[0024] Optionally, the dissolution time of Alg in distilled water is 5 min-30 min, for example, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min.

[0025] In one embodiment of the present invention, the dissolution time is 20 min.

[0026] Optionally, Alg is dissolved by stirring at a temperature of 25°C-60°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C.

[0027] In one embodiment of the present invention, the stirring and dissolving temperature is 50°C.

[0028] Optionally, the mass fraction of H2O2 is 5%-20%, for example, 5%, 10%, 15%, 20%.

[0029] In one example of the present invention, the mass fraction of H2O2 is 10%.

[0030] Optionally, the hydrolysis time is 16-30 h, for example, 16 h, 20 h, 24 h, 28 h, 30 h.

[0031] In one embodiment of the present invention, the hydrolysis time is 24 hours.

[0032] Optionally, the hydrolyzed product is dialyzed and purified for 1-4 days, such as 1 day, 2 days, 3 days, or 4 days. The hydrolyzed product of the present invention is guaranteed to be completely dialyzed and purified.

[0033] In one embodiment of the present invention, the dialysis time is 3 days.

[0034] Optionally, the particle size of the cell sieve is 0.2-0.44 μm, for example, 0.22 μm, 0.24 μm, or 0.44 μm.

[0035] The cell screen of the present invention can filter out impurities such as bacteria and other particles.

[0036] In one example of the present invention, the cell mesh particle size is 0.22 μm.

[0037] Optionally, in step S2, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride EDAC is added, and the reaction time with sodium alginate oligosaccharide AOS is 10-60 min, for example, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min.

[0038] In one embodiment of the present invention, the reaction time is 30 min.

[0039] Optionally, in the reaction system, the mass ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride EDAC to N-hydroxysulfosuccinimide NHS is 1-5:1-5; for example, 1:1, 1:2, 1:3, 1:4, 1:5, 2:1, 2:3, 2:5, 3:1, 3:2, 3:4, 3:5, 4:1, 4:3, 4:5, 5:1, 5:2, 5:3, 5:4.

[0040] In one example of the present invention, the mass ratio of EDAC to NHS is 2:3.

[0041] Optionally, the stirring time under nitrogen is 10-60 min, for example, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min.

[0042] In one embodiment of the present invention, the stirring time is 30 minutes.

[0043] Optionally, in step S2, the reaction time of sodium alginate oligosaccharide AOS and dopamine hydrochloride DA does not exceed 24 hours; optionally, the stirring time after adding dopamine hydrochloride is 1-30 hours, for example, 4 hours, 8 hours, 12 hours, 15 hours, 20 hours, 25 hours, 30 hours.

[0044] In one embodiment of the present invention, the stirring time after adding dopamine hydrochloride is 24 hours.

[0045] Optionally, the mass ratio of sodium alginate oligosaccharide AOS to dopamine hydrochloride DA is 10-15.

[0046] Optionally, the product is dialyzed and purified for 1-5 days, such as 1 day, 2 days, 3 days, 4 days, or 5 days.

[0047] In one embodiment of the present invention, the purification was performed by dialysis for 3 days.

[0048] Optionally, the polymerization adhesion position of the alginate oligosaccharide AOS and dopamine hydrochloride DA complex is tracked, and fluorescent FITC-PEG-NH2 is attached to AOS-DA to form AOS-DA-FITC.

[0049] In one example of the present invention, the specific steps of attaching fluorescent FITC-PEG-NH2 to AOS-DA to form AOS-DA-FITC are as follows: dissolving AOS-DA, EDAC and NHS in deionized water, and stirring under nitrogen until completely dissolved; then adding FITC-PEG-NH2 to the mixture solution, and continuously stirring the reaction under nitrogen at room temperature; collecting the reaction solution and dialyzing it in distilled water for 3 days, and obtaining the final product AOS-DA-FITC by freeze-drying.

[0050] Optionally, the concentration of AOS-DA is 5-20 mg / mL, for example, 5 mg / mL, 8 mg / mL, 10 mg / mL, 15 mg / mL, 20 mg / mL.

[0051] In one example of the present invention, the concentration of AOS-DA is 10 mg / mL.

[0052] Optionally, the concentration of FITC-PEG-NH2 is 0.1-1 mg / mL, for example, 0.1 mg / mL, 0.25 mg / mL, 0.5 mg / mL, 0.75 mg / mL, 1 mg / mL.

[0053] In one example of the present invention, the concentration of FITC-PEG-NH2 is 0.25 mg / mL.

[0054] Optionally, the stirring time of grafting FITC-PEG-NH2 is 1-30 h, for example, 1 h, 4 h, 8 h, 12 h, 15 h, 20 h, 25 h, 30 h.

[0055] In one embodiment of the present invention, the stirring time is 24 hours.

[0056] Optionally, the AOS-DA-FITC product is dialyzed and purified for 1-5 days, such as 1 day, 2 days, 3 days, 4 days, or 5 days.

[0057] In one embodiment of the present invention, the dialysis purification time is 3 days.

[0058] In a fifth aspect, an embodiment of the present invention provides a method for forming a coating, comprising: contacting a prepolymer of the polymer described in the third aspect with reactive oxygen species ROS and peroxidase, so that the prepolymer of the polymer undergoes oxidative polymerization to generate a polymer shown in formula I; the peroxidase is catalase CAT and / or horseradish peroxidase HRP.

[0059] The reactive oxygen species ROS are superoxide anion free radicals (O2 - ), hydrogen peroxide (H2O2), hydroxyl radical (·OH), singlet oxygen ( 1 O2), peroxynitrite (ONOO - ), hypochlorous acid (HOCl).

[0060] Optionally, the bladder mucosal injury includes inflammation, hemorrhage, edema, fibrosis and hypertrophy of bladder tissue.

[0061] In a sixth aspect, an embodiment of the present invention provides the use of a prepolymer of the polymer in preparing a bladder mucosal injury repair material.

[0062] (III) Beneficial effects

[0063] 1. The present invention modifies dopamine with natural polysaccharides, utilizes the in-situ polymerization of the endogenous environment at the site of inflammation, and forms a natural protective barrier at the site of bladder wall damage; the surface is polysaccharide, and the polydopamine adhered to the bladder wall has excellent anti-inflammatory and anti-oxidative stress effects, and can effectively repair the damaged bladder wall.

[0064] 2. A polymer, a polymer prepolymer, a preparation method and its use of the present invention, and a drug with anti-inflammatory and antioxidant effects have a therapeutic effect on IC. Under inflammatory conditions, peroxidase in tissues can increase local oxygen content, greatly improve the rate of dopamine polymerization, and form a solid coating at the lesion site.

[0065] 3. A polymer, a polymer prepolymer, a preparation method and a use thereof of the present invention, through the condition of bladder wall injury, in situ synthesizes a polymer film coating, and its loading part restores and improves the bladder volume and bladder wall thickness of rats with interstitial cystitis.

[0066] 4. A polymer, a polymer prepolymer, a preparation method and its use of the present invention, the loading part of the polymer film coating restores and improves the inflammation, hemorrhage, edema, fibrosis and mast cell count level of bladder tissue.

[0067] 5. A polymer, a polymer prepolymer, a preparation method and a use thereof of the present invention, and a polymer film coating loaded with the polymer partially restore and improve the expression of inflammatory factors in the bladder tissue of rats with interstitial cystitis.

[0068] 6. A polymer, a polymer prepolymer, a preparation method and uses thereof of the present invention provide a more economical and efficient mucosal adhesion drug delivery system. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 The present invention provides a polymer, a polymer prepolymer, a preparation method and use thereof, and a preparation process of AOS-DA and fluorescently labeled AOS-DA-FITC in Example 1;

[0070] Figure 2 The toxicity of AOS-DA to cells at different concentrations in Example 2 of the present invention is evaluated;

[0071] Figure 3 AOS-DA in vitro polymerization experiment under CAT and H2O2 conditions in Example 3 of a polymer, a polymer prepolymer, a preparation method and a use thereof of the present invention;

[0072] Figure 4 In-situ polymerization of AOS-DA-FITC in the case of disease in Example 4 of the present invention, a polymer, a prepolymer of the polymer, a preparation method and a use thereof;

[0073] Figure 5 In Example 5 of the present invention, a polymer, a polymer prepolymer, a preparation method and a use thereof, bladder tissue samples were sliced ​​and stained to perform histological evaluation. DETAILED DESCRIPTION

[0074] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0075] The following is a description of the preferred embodiments of the present invention.

[0076] Example 1

[0077] Preparation of Sodium Alginate Oligosaccharides by Hydrolysis of Sodium Alginate Using Hydrogen Peroxide as Oxidant

[0078] 450 mg of sodium alginate was dissolved in deionized water (1.5%, w / v) in a 50 mL round-bottom flask and stirred vigorously in a 50°C water bath. After stirring for 20 minutes, 30% hydrogen peroxide was added. The reaction solution was collected and dialyzed in distilled water for 3 days, then filtered with a 0.22 μm cell sieve and freeze-dried to obtain the product AOS.

[0079] Grafting of AOS onto dopamine DA via Schiff base reduction reaction

[0080] 100 mg of NHS and 150 mg of EDAC were added to the filtered solution, and the mixture was stirred for 30 minutes under a nitrogen atmosphere. Then, 40 mg of dopamine hydrochloride was added to the solution, and the reactant was further stirred for 24 hours under nitrogen bubbling. Finally, the product was freeze-dried after dialysis purification for 3 days to obtain AOS-DA.

[0081] The degree of substitution of DA in AOS-DA was determined by 1H NMR. Figure 1 a The calculated grafting rate of DA was 48.5%, and the chemical structure of AOS-DA was analyzed by FT-IR. Figure 1 b at 1730cm -1 A new spectral band appeared at the 40°C, indicating the formation of a carboxyl group; this indicates that the H2O2 treatment under extreme conditions destroyed the glycosidic bond, changed the structure of the reducing end residue, and formed a -COOH group.

[0082] Preparation of AOS-DA-FITC

[0083] In order to track the location of the polymer in vivo, fluorescent FITC was used for grafting tracking. 200 mg AOS-DA, 160 mg EDAC and 240 mg NHS were weighed and dissolved in 20 mL deionized water and stirred for 1 hour under nitrogen until completely dissolved. Then 5 mg FITC-PEG-NH2 was added to the mixture solution and continued to stir for 24 hours under nitrogen at room temperature. The reaction solution was collected and dialyzed in distilled water for 3 days, and the final product AOS-DA-FITC was obtained by freeze drying. Figure 1 As shown in b, the chemical structure of AOS-DA-FITC was analyzed by FT-IR.

[0084] Comparative Example

[0085] Preparation of bladder mucosal injury repair material using sodium alginate

[0086] Sodium alginate itself is a component of the bladder mucosal layer. When the bladder mucosa is damaged, the sodium alginate is reduced or damaged. The concentration of sodium alginate affects its viscosity. Sodium alginate alone cannot quickly form a gel to achieve an adhesion effect.

[0087] Preparation of bladder mucosal injury repair material using polydopamine

[0088] Lacking the original ingredient sodium alginate, the use of dopamine polymerization alone cannot simulate the inherent components of the bladder mucosa.

[0089] Sodium alginate is easily cross-linked and solidified with divalent cations or small molecules, and quickly forms a gel under extremely mild conditions. In the present invention, dopamine is developed as a small molecule precursor, and similar adhesion properties are achieved through polymerization. The sodium alginate on the surface simulates the inherent components of the bladder mucosa.

[0090] Test Example 1

[0091] Cytotoxicity evaluation

[0092] AM-PI staining was used to detect the activity and cytotoxicity of AOS, DA and AOS-DA on SV-HUC-1 cells (urothelial cells) and to evaluate their in vitro biocompatibility.

[0093] The prepared AOS, DA and AOS-DA were added to F-12K culture medium at different concentrations (e.g., 0 μg / mL, 50 μg / mL, 100 μg / mL, 250 μg / mL, 500 μg / mL, 1000 μg / mL). The solution was sterilized by filtering bacteria with a 0.22 μm filter and then stored at 4 ° C. SV-HUC-1 urothelial cells with a good logarithmic growth phase were seeded in a 24-well plate at a density of 1.0×104 cells / well and incubated for 24 hours. Thereafter, the AOS, DA and AOS-DA solutions prepared above at different concentrations were added to 1 mL of culture medium, and after incubation for another 24, the cells were washed 3 times with PBS buffer, and the prepared AM-PI solution was added to each well, incubated for 15 minutes, and the image was captured using a fluorescence microscope. Figure 2 It was clearly observed that after 24 hours of incubation, there were almost no dead cells in AOS, DA, and AOS-DA, indicating that AOS, DA, and AOS-DA had almost no biotoxicity to urothelial cells and had good biocompatibility.

[0094] Test Example 2

[0095] In vitro polymerization of polydopamine (PDA) catalyzed by peroxidase (CAT) in the presence of H2O2

[0096] 10 mg dopamine hydrochloride and 50 mg AOS-DA were quickly dissolved in pH 7.4 phosphate buffer (PBS, 1 mL), and then H2O2 (1 M, 20 μL) and CAT (1 mg / mL, 25 μL, dissolved in 1X PBS) were quickly added. Figure 3 a (middle); control group as Figure 3 a (left) shows that CAT and H2O2 were not added; the control group Figure 3 a (right) shows that CAT is not added. The solutions were placed in a low partial pressure oxygen container, and the reaction mixture was kept at 37°C for 10-180 minutes. It can be observed that dopamine polymerization was accelerated by 350 times under the conditions of adding CAT and H2O2.

[0097] Normal bladder (NC group) and bladder tissue with inflammation (IC group) were soaked in phosphate buffered saline with the same concentration of DA and AOS-DA for 10-180 minutes. Figure 3 As shown in b. Inflammation and oxidative stress occur in the bladder under disease conditions, and the expression of CAT enzyme and DHE staining ROS increases, which is more conducive to aggregation.

[0098] Test Example 3

[0099] In vivo tissue adhesion properties

[0100] After the bladder was emptied by gentle abdominal pressure, 0.5 ml of the preparation (AOS-DA-FITC dissolved in saline at a concentration of 250 μg / mL) was instilled into the bladder with disease inflammation using a PE-50 urinary catheter. Figure 4 As shown in a, a black adhesion layer is formed in the bladder. When the bladder is emptied, the adhesion layer still exists on the bladder wall. The bladder tissue samples are frozen and embedded, and then cut into 10 μm thick sections and observed under an electron microscope. Figure 4 As shown in b, polymerized dopamine particles are formed on the bladder wall.

[0101] Test Example 4

[0102] Immunofluorescence staining The bladder tissue samples were fixed with 4% paraformaldehyde for 24 h and then embedded in paraffin; after that, the tissue samples were cut into 5 μm sections for further histological staining and analysis; the sections were collected on slides and then stained with hematoxylin and eosin aqueous solution, as Figure 5 a shows the overall bladder tissue morphology. The bladder wall thickness (detrusor muscle and mucosa) was measured in different groups. The thickness of the bladder wall was statistically analyzed as follows: Figure 5 As shown in e, the bladder wall of the disease group recovered to near-health through the repair of polydopamine (control group).

[0103] like Figure 5 As shown in b, the sections were stained with Masson trichrome for fibrosis evaluation. The degree of fibrosis was statistically shown in Figure 5 As shown in f, the degree of fibrosis in the disease group was restored to nearly the healthy level (control group) through the repair of polydopamine, while the fibrosis in the disease group was more serious, reaching 40%.

[0104] For immunofluorescence, bladder samples were fixed in 4% paraformaldehyde and then cryoprotected, frozen, sectioned, and incubated with primary antibodies (1:100) overnight at 4°C. Sections were then incubated with secondary antibodies (1:2000), and nuclei were stained with DAPI; Figure 5 As shown in c, mast cells were imaged and observed under a fluorescence microscope. Mast cell statistics are shown in Figure 5 As shown in g, the disease group had more mast cells and severe edema, while the experimental group was consistent with the healthy group.

[0105] The histological inflammation score was used to calculate the Figure 5 As shown in (d), there was slight to mild inflammatory infiltration in the lamina propria, accompanied by scattered neutrophils or lymphocytes, and mild edema or hemorrhage, but there was no inflammation or obvious urothelial changes in the muscularis propria. The disease group recovered to near health (control group) through polydopamine repair.

[0106] In summary, the experiments showed that the loading of polymer film coating partially restored and improved the inflammation, hemorrhage, edema, fibrosis and mast cell count levels of bladder tissue.

[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polymer, characterized in that The polymer has a chemical structure as shown in Formula I: Wherein x=1-10; y=10-200.

2. Use of the polymer according to claim 1 in preparing bladder mucosal injury repair materials.

3. A prepolymer solution for forming the polymer according to claim 1, characterized in that: It contains prepolymers of sodium alginate oligosaccharide and dopamine.

4. The prepolymer solution according to claim 3, characterized in that: The prepolymer of the polymer further contains 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride EDAC as an activator and N-hydroxysulfosuccinimide NHS as a catalyst.

5. A method for preparing a prepolymer solution according to any one of claims 3 to 4, characterized in that: The preparation method comprises the steps of: S1, providing sodium alginate oligosaccharide AOS aqueous solution; S2, deoxygenating the alginate oligosaccharide AOS aqueous solution; adding an activator 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride EDAC, stirring; adding a catalyst N-hydroxysulfosuccinimide NHS, stirring; then adding dopamine hydrochloride DA, stirring, dialyzing and purifying after the reaction is complete, and then freeze-drying for 2 days to 6 days to obtain the prepolymer solution.

6. The method for preparing the prepolymer solution according to claim 5, characterized in that: In step S1, the preparation method of sodium alginate oligosaccharide AOS is as follows: sodium alginate Alg is dispersed in distilled water, stirred at 25°C-60°C, and after being completely dissolved, hydrogen peroxide is added, and after the reaction is complete, the product solution is dialyzed for purification, and then filtered through a cell sieve with a particle size of 0.2-0.44 μm to obtain the product sodium alginate oligosaccharide AOS; The mass fraction of sodium alginate Alg dissolved in distilled water is 0.5%-2.5%, and the mass fraction of H2O2 is 5%-20%.

7. The method for preparing the prepolymer solution according to claim 5, characterized in that: In step S2, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride EDAC is added, and the reaction time with sodium alginate oligosaccharide AOS is 30-60 min; in the reaction system, the mass ratio of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride EDAC to N-hydroxysulfosuccinimide NHS is ≥15.

8. The method for preparing the prepolymer solution according to claim 5, characterized in that: In step S2, the reaction time of sodium alginate oligosaccharide AOS and dopamine hydrochloride DA does not exceed 24 hours; the mass ratio of sodium alginate oligosaccharide AOS to dopamine hydrochloride DA is 10-15.

9. A method for forming a coating, comprising: The prepolymer solution according to claim 3 or 4 or the prepolymer solution prepared by the preparation method according to any one of claims 5 to 8 is contacted with active oxygen ROS and peroxidase, so that the prepolymer solution undergoes oxidative polymerization to generate a polymer shown in formula I; the peroxidase is catalase CAT and / or horseradish peroxidase HRP.

10. Use of the prepolymer solution according to any one of claims 3-4 in preparing bladder mucosal injury repair material.